Intraspinal gas - (:unkn) unknown (ELSEVIER SCI LTD, 2007)
Intraspinal gas can be observed in a number of pathological settings including degenerative disc disease, infection, tumor or trauma, and in patients who have undergone therapeutic and diagnostic procedures. The air can be epidural, intradural or intradiscal. Intraspinal gas is usually asymptomatic. We report intraspinal gas in three patients, one with cervical, one with thoracic, and one with lumber disc disease and spondylolisthesis. The investigations were all completed at the the same medical center and CT and MRI were done in each case. The gas was in the epidural space in all three patients. These cases provide further evidence that intraspinal gas may persist without causing symptoms, and that resultant symptoms can disappear spontaneously. MRI is not reliable for diagnosing intraspinal gas; CT is recommended. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: degenerative disc disease; intraspinal gas; low back pain; NERVE ROOT COMPRESSION; EPIDURAL GAS; DISK HERNIATION; SCIATICA; AIR; CT